High specific power electrical machines: A system perspective - El-Refaie, Ayman; Osama, Mohamed (CES Transactions on Electrical Machines and Systems, 2019)
There has been a growing need for high specific power electrical machines for a wide range of applications. These include hybrid/electric traction applications, and aerospace applications. A lot of work has been done to accomplish significantly higher specific power electrical machines especially for aerospace applications. Several machine topologies as well as thermal management schemes have been proposed. Even though there has been a few publications that provided an overview of high-speed and high specific power electrical machines [1-3], the goal of this paper is to provide a more comprehensive review of high specific power electrical machines with special focus on machines that have been built and tested and are considered the leading candidates defining the state-of-the art. Another key objective of this paper is to highlight the key "system-level" tradeoffs involved in pushing electrical machines to higher specific power. Focusing solely on the machine specific power can lead to a sub-optimal solution at the system-level.